Communication Petterns Of Coaches And Students In Cultivating Discipline Of Memorizing The Qur’an - Qudratullah Qudratullah; Nor Aswinda; Najamuddin Najamuddin (IAIN Salatiga, 2020)
This research aims to determine the pettern of communication between Coaches and students in disciplining the memorization of the Qir’an at the Baitul Al-Muqarramah Foundation in Bone Regency. Qualitative research methods are used in this research by conducting interviews. Interviews wew conducted with informants who were Coaches at the Baitul Al-Muqarramah Foundation in Bone Regency. The results showed the Coaches in the Baitul Al-Muqarramah Foundation used verbal and nonverbal communication. There are two communication petterns that are used there are also two namely interpersonal communication petterns and group communication petterns. The petterns of group communication is more dominant used in this foundation, while interpernonal communication is usually applied to students who are less optimal in directing group communication. Where the pettern of group communication is more dominant applied in the process of direction every day. As with interpersonal communication, this communication pettern is usually applied to a particular situation. For axample, there is one student who cannot be fostered if trough the communication petterns of the group. Proven trought group communication implemented by the Coach, able to discipline student to memorize the Qur’an and make student achieve targets that have been determined with a dominant scale. Even trought this group communication, the time of a Coach can be more efficient than interpersonal communication which requires the trainer to meet one-onone with his students. The obstacle factors of the Coaches are so unable to discipline the memorization of the Qur’an by their students namely; first, the psychological factors and habit factor od the students.